Electrophysiological properties of phentolamine in man. Issue 9 (September 1977) - Gould, L; Reddy, C V; Chua, W; Swamy, C R; Dorismond, J C
Abstract : The effects of phentolamine, 0-3 mg/min given intravenously for 15 minutes, on His bundle electrograms were studied in 11 patients with heart disease. Recordings were made at varied heart rates, using atrial pacing. Phentolamine significantly reduced the AH interval in every patient but it had no effect on the HV interval. Functional and effective refractory periods were measured with the use of the atrial extrastimulus technique. The effective refractory period of the atrium and atrioventricular node as well as the functional refractory period of the atrioventricular node all significantly decreased after phentolamine infusion. This improvement in conduction is probably mediated by a release of catecholamines.